2003
DOI: 10.1071/ar02108
|View full text |Cite
|
Sign up to set email alerts
|

Macadamia responses to mild water stress at different phenological stages

Abstract: Abstract. Mild water stress was imposed on bearing macadamia trees in through-draining lysimeters at various phenological stages. Water was withheld until a xylem water potential (Ψ x ) of -1.5 to 2.0 MPa was reached, this being maintained by partial water replenishment at 2-day intervals. Flowering, nut set, nut development, yield, and quality responses were assessed to identify critical, stress-sensitive stages. Stress during nut maturation was particularly detrimental to both yield and quality, although str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 12 publications
1
30
1
1
Order By: Relevance
“…No total das cinco safras, houve aumento da produtividade de amêndoas em 130% das nogueiras consorciadas e em 176% das nogueiras solteiras, com a irrigação. Segundo Stephenson et al (2003), mesmo curtos períodos de estresse hídrico, em qualquer uma das fases reprodutivas (iniciação e desenvolvimento floral e expansão, e maturação dos frutos), reduz a produtividade da nogueira-macadâmia. Isso pode explicar os resultados obtidos, uma vez que, entre agosto e setembro da maioria dos anos avaliados, nos estádios de florescimento e início do crescimento dos frutos (Tabela 1), houve reduzida precipitação pluvial, o que provavelmente causou estresse por seca às plantas de macadâmia nos cultivos não irrigados.…”
Section: Methodsunclassified
“…No total das cinco safras, houve aumento da produtividade de amêndoas em 130% das nogueiras consorciadas e em 176% das nogueiras solteiras, com a irrigação. Segundo Stephenson et al (2003), mesmo curtos períodos de estresse hídrico, em qualquer uma das fases reprodutivas (iniciação e desenvolvimento floral e expansão, e maturação dos frutos), reduz a produtividade da nogueira-macadâmia. Isso pode explicar os resultados obtidos, uma vez que, entre agosto e setembro da maioria dos anos avaliados, nos estádios de florescimento e início do crescimento dos frutos (Tabela 1), houve reduzida precipitação pluvial, o que provavelmente causou estresse por seca às plantas de macadâmia nos cultivos não irrigados.…”
Section: Methodsunclassified
“…Tree growth, thus described by the function, is first estimated for median annual rainfall of the site and then adjusted in response to the variation in annual rainfall from 1 year to the next. Parameter set values for W(0), K and α were elicited from subject matter experts and validated with data from growth of other plantation or orchard tree crops including macadamia, almond and olive [13,22,35,41,47].…”
Section: Tree Growth Modelmentioning
confidence: 99%
“…Yield estimates from India are often sourced from individual trees rather than being based on the average of a plantation over several seasons [30,34]. For comparison purposes, it is worth noting that the seed yield of commercial orchards of macadamia and almonds tends to range between 5 and 20 kg of nuts in shells per tree per annum, equivalent to about 1 to 6 t per hectare at planting densities of 200 to 320 trees per hectare [13,22,35,41,47]. The lower yield estimates are for non-irrigated groves.…”
Section: Introductionmentioning
confidence: 99%
“…In many areas of macadamia cultivation in Australia, South Africa and Hawaii, the amount and/or distribution of rainfall are insufficient to sustain high nut yields (Stephenson et al, 1986(Stephenson et al, , 2003. According to Stephenson et al (2003), nut yields were reduced by 45% when water deficit stress occurred during the premature fruit-drop period (early fruit growth), and kernel recovery was reduced from 34% to 25% when water deficit occurred during the oil accumulation stage. These authors concluded that short periods of water deficit stress during any reproductive stage reduce the yield of macadamia trees.…”
Section: Introductionmentioning
confidence: 96%
“…According to , Stephenson et al (2003) and Mayer et al (2006), macadamia yield is greatly affected by climatic conditions, particularly by water deficits. According to São José (1991), the use of irrigation during flowering and fruit growth in Brazilian macadamia cultivation can increase fruit set and reduce premature fruit drop.…”
Section: Introductionmentioning
confidence: 99%